How Does Green Human Resources Management Practice Influence The Job Pursuit Intention of Millennial Generation in Indonesia and Malaysia? - Kartika, Lindawati; Wahyuningsih, Fita; Rashid Abdullah, Abdul (Journal of Technology Management and Business, 2023)
Green Human Resource Management (GHRM) practice is a set of activities in human resources that involve environmental aspects in their implementation. In 2020, with the millennial generation making up the largest proportion of the workforce, they will wield significant influence over business trends. Previous research indicates that job pursuit intentions are influenced by organisational attributes, emphasising the need for companies to understand the important values held by their future workforce. The purpose of this study is to measure millennials’ perceptions of the influence of GHRM practices on their intention to seek employment in Indonesian and Malaysian companies and to analyse the impact of the implementation of GHRM practices in the company on millennials’ intention to seek employment, using pro-environmental consciousness as a moderator. The data used in this research were primary data obtained through questionnaires with the Likert scale and the scenario-based study, and secondary data from the central statistical board and other literature that supports the research. The respondents in this study were final-year students at IPB University Indonesia and University Putra Malaysia. Data were analysed using descriptive analysis, hierarchical linear regression analysis, and bootstrapping in SPSS 22. The results show that GHRM is positively significant with job pursuit intention (JPI), whereas personal pro-environmental consciousness was not given the significant effect between GHRM and JPI. Implementing GHRM practices is indispensable for companies seeking to attract millennial talent. These practices can be implemented using both push and pull strategies, embedding pro-environmental aspects.